Soil compaction caused by the impact of machinery traffic during corn (Zea mays) harvest = Compactación del suelo causado por el tránsito de maquinarias en la cosecha de maíz (Zea mays) - Hidalgo, Ramón Jesús; Pozzolo, Oscar Ruben; Domínguez, José Fabio; Giménez, Laura; Botta, Guido Fernando (Facultad de Ciencias Agrarias, Universidad Nacional de Cuyo, 2020)
The aim of this work was to study soil compaction caused by the traffic of two types of combine harvesters and a tractor plus a grain cart with two loading conditions (fully loaded hoppers-empty hoppers) during corn harvest on vertic argiudoll soil by means of direct seeding system. Soil penetration resistance (PR) and soil bulk density (BD) were measured to a depth of 40 cm in five sampling sites. Response variables determinations were also analyzed. The tractor and the fully loaded grain cart traffic caused greater soil compaction in all the sampling depths, exceeding 60 cm on both sides of the footprint center. What is more, the values obtained from PR and BD measurements were higher than those values considered suitable for normal root growth. This was only evident in the tread width of the tires during the passing of the two fully loaded combine harvesters. The analysis of inflation pressures and tire loads used, indicated in some cases, poor concordance between these variables. The analysis also indicated that the tires were inflated to the limit of resistance.